Impact of gender and age on the occurrence of gastric polyps: data analysis of 69575 southeastern Chinese patients - Zheng, Endian; Ni, Shuangshuang; Yu, Yingcong; Wang, Ying; Weng, Xuejian; Zheng, Liang (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: Current epidemiological data suggest that the incidence of gastric polyps (GP) is rare, and its etiology and pathogenesis are still not clear. This study analyzed and compared the occurrence and pathological types of GPs in southeast Chinese patients according to gender and age. Materials and Methods: This was a retrospective study of patients diagnosed with GP (n=2125) in Wenzhou People’s Hospital (China) between January 2004 and December 2013. The relationships between the detection rate, the characteristics of GP, and the patients’ demographic data were analyzed. Results: The detection rate of GP was 2.3% and 3.9% in males and females, respectively (p<0.01). The detection rate increased with increasing age in both genders. Polyps in the gastric antrum and gastric body were the most prevalent in both genders. Similarly, inflammatory polyps and hyperplastic polyps were the most prevalent in both genders. Hyperplastic polyps were more common in females than in males (28.6% vs. 24.2%, p<0.05), while there was no difference for inflammatory polyps, fundic GP, and adenoma (p>0.05). Age had no impact on the pathology of GP (p>0.05). Conclusions: The incidence of GPs was associated with gender and age.